Spatial transcriptomics of dorsal root ganglia identifies molecular signatures of human nociceptors - Tavares-Ferreira, Diana; Shiers, Stephanie; Ray, Pradipta R; Wangzhou, Andi; Jeevakumar, Vivekanand; Sankaranarayanan, Ishwarya; Cervantes, Anna M; Reese, Jeffrey C; Chamessian, Alexander; Copits, Bryan A; Dougherty, Patrick M; Gereau, 4th, Robert W; et al. (Science translational medicine, 2022)
Nociceptors are specialized sensory neurons that detect damaging or potentially damaging stimuli and are found in the dorsal root ganglia (DRG) and trigeminal ganglia. These neurons are critical for the generation of neuronal signals that ultimately create the perception of pain. Nociceptors are also primary targets for treating acute and chronic pain. Single-cell transcriptomics on mouse nociceptors has transformed our understanding of pain mechanisms. We sought to generate equivalent information for human nociceptors with the goal of identifying transcriptomic signatures of nociceptors, identifying species differences and potential drug targets. We used spatial transcriptomics to molecularly characterize transcriptomes of single DRG neurons from eight organ donors. We identified 12 clusters of human sensory neurons, 5 of which are C nociceptors, as well as 1 C low-threshold mechanoreceptors (LTMRs), 1 Aβ nociceptor, 2 Aδ, 2 Aβ, and 1 proprioceptor subtypes. By focusing on expression profiles for ion channels, G protein-coupled receptors (GPCRs), and other pharmacological targets, we provided a rich map of potential drug targets in the human DRG with direct comparison to mouse sensory neuron transcriptomes. We also compared human DRG neuronal subtypes to nonhuman primates showing conserved patterns of gene expression among many cell types but divergence among specific nociceptor subsets. Last, we identified sex differences in human DRG subpopulation transcriptomes, including a marked increase in calcitonin-related polypeptide alpha ( ) expression in female pruritogen receptor-enriched nociceptors. This comprehensive spatial characterization of human nociceptors might open the door to development of better treatments for acute and chronic pain disorders.